The contents of vocabulary work with primary school’s pupils at special schools - Бєляк, Ольга (Pedagogy of Higher and Secondary Education, 2014)
Belyak O. М. The contents of vocabulary work with primary school’s pupils at special schools The paper presents contents of work with primary school’s pupils at special schools. According to the purpose, the author makes the analysis of normative documents, which emphasize the need for constant vocabulary work. In addition, the author defines the stages and directions of vocabulary work at primary special schools and develops a set of exercises to specify and enrich the vocabulary of junior schoolchildren.